Incomplete Sanctions for the Non-Procedural Transfer of Non-Public Village Treasury Land - Adinda Salma Rachmantya; Hamidi Masykur; Supriyadi (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study aims to analyze the regulatory gap concerning sanctions in the transfer of village treasury land for non-public purposes that are not conducted in accordance with procedures under Minister of Home Affairs Regulation No. 3 of 2024, and to formulate an ideal sanction framework to ensure legal certainty and the protection of village assets. This research employs a normative juridical method with statutory, conceptual, and case approaches, supported by primary, secondary, and tertiary legal materials, and analyzed descriptively. The findings indicate that although the regulation provides more detailed procedures for the transfer of village treasury land, there is still a normative gap regarding firm sanctions for procedural violations. This condition weakens legal enforceability, creates opportunities for abuse of authority, and generates legal uncertainty in practice, as reflected in the case of Pandanlandung Village. Therefore, a reconstruction of sanction arrangements is required, encompassing administrative, civil, and criminal classifications, along with an integrated law enforcement mechanism. Such regulation is expected to enhance regulatory effectiveness, strengthen the protection of village assets, and ensure legal certainty in the management of village treasury land.